Outcomes and readmissions after transcatheter and surgical aortic valve replacement in patients with cirrhosis: A propensity matched analysis. Issue 1 (28th August 2017) - Dhoble, Abhijeet; Bhise, Viraj; Nevah, Moises I.; Balan, Prakash; Nguyen, Tom C.; Estrera, Anthony L.; Smalling, Richard W.
Abstract: Background: The data on the comparative outcomes and readmissions after transcatheter aortic valve replacement (TAVR) and surgical aortic valve replacement (SAVR) in patients with cirrhosis are limited. We compared mortality, complications, discharge disposition, 30‐day readmission rates, length of stay, and cost of hospitalization in cirrhotic patients undergoing TAVR and SAVR. Methods: The National Inpatient Sample (NIS) and the National Readmission Database (NRD) were used for the study. The International Classification of Diseases‐9th version was used to define cohorts of patients undergoing TAVR and SAVR. Patients undergoing concomitant other valve or coronary bypass surgery were excluded. Propensity‐score matching was used to compare the outcomes between the groups. Results: From 2012 to 2014, a total of 126 and 157 patients with cirrhosis underwent TAVR and SAVR, respectively. Of the 283 patients, 16 (5.7%) died during the same hospitalization. We found 345 patients with cirrhosis who had undergone an aortic valve replacement (156 with TAVR, and 189 with SAVR) in the 2013 and 2014 NRD. On propensity matching, there were no significant differences between the in‐hospital mortality, readmissions, hospitalization costs, and discharges to home within the TAVR and SAVR groups. However, post‐procedure length of stay (6.3 vs. 10.2 days; P  < 0.001) and blood transfusion rates (22% vs. 58%; P  < 0.001) were significantly lower in TAVR patients. Conclusions: Cirrhotic patients undergoing TAVR has high, but similar mortality and 30‐day readmission rates when compared to SAVR; however, has shorter length of stay and lower blood transfusion rates.